THE PROBLEM OF THE STRUCTURAL ANALYSIS OF «PSYCHOLOGICAL WELL-BEING» CONCEPT - Гуляєва, Олена Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
In the article there were analysed objective and subjective predictors of psychological well-being. There were considered the factors of psychological well-being: socio-economic, socio-cultural, biological and psychological. The psychological factor determines the structural and functional components of psychological well-being. The structural components include the emotional, cognitive and behavioral components; to the functional components, that provide positive functioning of personality, we refer autonomy, environmental management, personal growth, positive relations with others, the existence of life goals and self-image.